Respons Siswa Terhadap Model Pembelajaran Group Investigation Berbantuan Siniar Dalam Kegiatan Menulis Teks Berita - Syahda Deviana Salsabila; Diena San Fauziya (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2024)
The ability to write news texts for class VIII middle school students is still low. This problem was discovered based on observations when researchers talked to students at class VIII of SMP Negeri 1 Ngamprah, they did not understand the steps that had to be taken when writing news. In the learning process, teachers still use the lecture method, this makes students less active and tend to be passive when the teaching and learning process is taking place between the teacher and students. The learning model that can be a solution to this problem is the Group Investigation model assisted by broadcasts as a learning medium. The aim of this research is to determine students' responses to the application of the Group Investigation learning model assisted by podcasts in news text writing activities. This research uses a qualitative descriptive method with a research instrument in the form of a questionnaire. The results show an average of 63.83% included in the "Good" category.